Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
-7/9(x=3)=14
-7/9x-7/3=14 (distribute)
-7/9x=49/3 (add 7/3 to both sides)
x=-21 (divide 49/3 by -7/9)
you can check if its correct by substituting back into the original equation
-7/9x-7/3=14 (distribute)
-7/9x=49/3 (add 7/3 to both sides)
x=-21 (divide 49/3 by -7/9)
you can check if its correct by substituting back into the original equation
[tex]-\frac{7}{9}(x+3)=14\ \ \ \ \ |multiply\ both\ sides\ by\ (-\frac{9}{7})\\\\(-\frac{\not9^1}{\not7_1})\times(-\frac{\not7^1}{\not9_1})(x+3)=-\frac{9}{7}\times14\\\\x+3=-9\times2\\\\x+3=-18\ \ \ \ \ |subtract\ 3\ from\ both\ sides\\\\\boxed{x=-21}[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.